Optimum Capital Structure Adjustment Speed on Companies Listed in Indonesia Stock Exchange - Suramaya Suci Kewal (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2019)
AbstractThis study examines the existence of adjustments in the speed of the company's capital structure to achieve an optimal capital structure in accordance with the dynamics of trade-off and other factors affecting the company's capital structure adjustment. The optimal capital structure is estimated by using several variables, namely tangibility, firm size, profitability, liquidity, asset utilization, and business risk. The factors used to predict the optimal capital structure adjustment speed in this study are the distance between the capital structure and the optimal capital structure and financial deficit. The data analysis technique in this study is multiple linear regression with a significance level of 5%. The obtained results indicate that companies on the IDX are adjusting towards the optimal capital structure. The speed of adjustment is 0.128 so it can be concluded that the company's adjustment remains below its optimal debt level. The test results also prove that distance and financial deficit/surplus have no influence on the company's capital structure adjustment speed. Keywords: capital structure, dynamics trade offKecepatan Penyesuaian Struktur Modal Optimal Perusahaan di Bursa Efek IndonesiaAbstrakPenelitian ini menguji keberadaan penyesuaian kecepatan struktur modal perusahaan menuju ke struktur modal optimal sesuai dengan dynamics trade off dan faktor-faktor yang mempengaruhi kecepatan penyesuaian struktur modal optimal perusahaan. Struktur modal optimal diestimasi dengan menggunakan beberapa variabel yaitu tangibility, firm size, profitability, liquidity, asset utilization, dan business risk. Faktor-faktor yang digunakan untuk menduga kecepatan penyesuaian struktur modal optimal pada penelitian ini adalah jarak antara struktur modal dengan struktur modal optimal (distance) dan financial deficit/surplus. Teknik analisis data yang digunakan pada penelitian ini adalah regresi linier berganda dengan tingkat signifikansi sebesar 5%. Hasil yang diperoleh menunjukkan perusahaan-perusahaan di BEI melakukan penyesuaian menuju struktur modal optimal. Kecepatan penyesuaian sebesar 0,128 sehingga dapat disimpulkan bahwa perusahaan-perusahaan melakukan penyesuaian masih di bawah tingkat hutang optimalnya. Hasil pengujian juga membuktikan bahwa tidak terdapat pengaruh distance dan financial deficit/surplus terhadap kecepatan penyesuaian struktur modal perusahaan. Kata Kunci: struktur modal, dynamics trade off